Novel compact "via-less" ultra-wide band filter utilizing capacitive microstrip patch - Mohammad Shahrazel, Razalli; Alyani, Ismail; Mohamed Adzir, Mahdi; Mohd Nizar, Hamidon (EMW Publishing, 2009)
Full text of this article is also available at http://ceta.mit.edu/PIER/